Transformations of Less-Activated Phenols and Phenol Derivatives via C-O Cleavage - Qiu, Zihang; Li, Chao-Jun (Chemical reviews, 2020)
Employing phenols and phenol derivatives as electrophiles for cross-coupling reactions has numerous advantages over commonly used aryl halides in terms of environmental-friendliness and sustainability. In the early stage of discovering such transformations, most efforts have been devoted to utilizing highly activated sulfonate types of phenol derivatives (e.g., OTf, OTs, etc.), which have similar reactivities to the corresponding aryl halides. However, a continuing scientific challenge is how to achieve the direct C-O functionalizations of relatively less-activated phenol derivatives more efficiently. In this review, we will focus on the recent updates on the C-O functionalizations of less-activated phenol derivatives, from aryl carboxylates (e.g., pivalates, acetates, etc.), aryl carbamates and carbonates, to aryl ethers (anisoles, diaryl ethers, aryl pyridyl ethers, aryl silyl ethers), to phenolate salts, and ultimately to simply unprotected phenols, sorted by the types of bond formations. Both transition-metal-catalyzed and transition-metal-free protocols will be covered and discussed in detail. Instead, the C-O functionalizations of aryl sulfonates will not be covered extensively unless they are closely related, due to their high reactivity. Since aryl ethers and phenols represent the main linkages or units in lignin biomass, the successes of such transformations will potentially make major contributions to the direct lignin biomass upgrading and depolymerization.